Characterizing the Flood Hazard Risk Zones Using ArcGIS Pro Software: A Case Study of Baling Kedah, Malaysia - Azri, Airell Harith; Abdul Halim, Saiful Shahaziq; HUSAIN, MOHD NAJIB (Research in Management of Technology and Business, 2024)
Floods are the most recurrent kind of natural disasters for it is the overflow of water that gets to cover areas usually perceived as dry. In order to increase the community’s resilience against future flood disasters, this research aim to create a flood hazard mapping of Baling, Kedah, Malaysia. This study’s primary goal is to identify flood risk factors and investigate the areas of Baling Kedah that are more likely to experience a flood disaster. The specific objectives of the study are to identify which part of Baling has the higher risk of flood disaster and further to produce a flood hazard mapping in Baling Kedah Malaysia. The study was carried out in stages by compiling data from a variety of open sources, including ArcMap, NASA Power Dave, the USGS, ESRI Sentinel-2 Land Cover Explorer, and precipitation, land use, and boundary data, in various formats to perform data processing. Many methods have been used to process the data obtained from many open sources in the past to provide data on precipitation, river distance, flow length, slope, elevation, and land use using ArcGIS Pro software. Following that, the flood hazard map for Baling, Kedah, is created using the Reclassify and Weighted Sum tools, both of which are included in the ArcGIS Pro software. Data analysis can be done using the flood hazard map to extract important information that is contained within the map. This study’s primary finding indicated the possibility and risk of flooding in the Baling Kedah area. To sum up, this study was critical in mapping flood dangers and pinpointing the parts of Baling most vulnerable to floods.